KIẾN TẠO HIỆN ĐẠI VÀ CÁC TAI BIẾN ĐỊA CHẤT LIÊN QUAN Ở VÙNG BIỂN VIỆT NAM VÀ LÂN CẬN - Trịnh, Phan Trọng; Hướng, Nguyễn Văn; Liêm, Ngô Văn; Tô, Trần Đình; Hải, Vy Quốc; Vinh, Hoàng Quang; Thơm, Bùi Văn; Xuyên, Nguyễn Quang; Thuận, Nguyễn Viết; Thảo, Bùi Thị (Vietnam Journal of Earth Sciences, 2012)
SUMMARY Neotectonics and geological hazards in Vietnam Sea and surroundings This paper presents velocities of present-day tectonic movements in Vietnam and surroundings determined from GPS campaigns from 2007 to 2010. Absolute displacements and velocities of GPS stations in the IGS05 frame were determined. The result indicates that Lang station (LANG) moves eastward with slip rate of 39mm/yr, southward with slip rate of 11 mm/yr. The rate of Bach Long Vi (BLV1) is 30mm/yr for the eastern component and 11mm/yr for southern component. Song Tu Tay (STT1) moves eastwards with the rate of 24mm/yr and southwards of 8mm/yr. Con Dao (CDA1) moves to the east with the rate of 22mm/yr and to the south with the rate of 6mm/yr. Dong Hoi (DOHO) move to the east with the rate of 27mm/yr and to the south with the rate of 8mm/yr. Hue (HUES) moves to the east with the rate of 30 mm/yr and to the south with the rate of 12mm/yr. HOCM move to the east with the rate of 22mm/yr and to the south with the rate of 10mm/yr. Calculate errors for both direction vary in 0.6 - 1mm/y. Based on seismic profiles, focal mechanisms and regional stress field, several fault segments in Pliocene - Quaternary sediments in East Vietnam Sea has been identified in Red River, Cuu Long and Nam Con Son basins with maximum of 15 km in length. Actual stress regimes in Vietnam and south Hainan basins being transitional demonstrate no source of large tsunami closing to Vietnam shelf. The subduction zone located at north Borneo is not active at present. Only Manila subduction zone is the source for large tsunami in East Vietnam Sea. Based on gravimetric field, topography, distribution of focal mechanisms in various depths and the rate of actual tectonic movement, 5 fault zones of the Manila subduction zone have been divided. The fault zones F3 and F4 can produce respectively maximum earthquake of 8.1 and 8.4. Modeling of displacement of fault zone F4 from the depth 15 to 20 km, 2m high of tsunami at Quang Ngai can be occurred. The depth of tsunami flood can be up to 4-5 m at some places in Quang Ngai and Da Nang.